The role of ecological niche evolution on diversification patterns of birds distinctly distributed between the Amazonia and Atlantic rainforests - da Silva, Ricardo Ribeiro (PLoS One, 2020)
The Amazonian and Atlantic Forest share several organisms that are currently isolated but were continuously distributed during the Quaternary period. As both biomes are under different climatic regimes, paleoclimatic events may have modulated species' niches due to a lack of gene flow and imposing divergent selection pressure. Here, we assessed patterns of ecological niche overlap in 37 species of birds with disjunct ranges between the Amazonian and Brazilian Atlantic Forests. We performed niche overlap analysis and ecological niche modeling using four machine-learning algorithms to evaluate whether species' ecological niches evolved or remained conserved after the past South American biogeographic events. We found a low niche overlap among the same species populations in the two biomes. However, niche similarity tests showed that, for half of the species, the overlap was higher than the ones generated by our null models. These results lead us to conclude that niche conservatism was not enough to avoid ecological differentiation among species even though detected in many species. In sum, our results support the role of climatic changes in late-Pleistocene—that isolated Amazon and the Atlantic Forest—as a driving force of ecological differences among the same species populations and potential mechanism of current diversification in both regions.